Factors Controlling Runner Formation in Strawberries - Yali Li (Agronomy, 2025)
Strawberry propagation relies predominantly on asexual reproduction via runner plants, making runners a critical organ for cultivation. Runners develop from axillary buds under specific environmental conditions. While long-day photoperiods and higher temperatures are key factors for inducing runner formation in most strawberry varieties, certain everbearing cultivars exhibit enhanced runner formation even under short-day conditions. Gibberellin (GA) is indispensable for runner bud outgrowth, with cytokinin and auxin synergistically regulating runner outgrowth. Genetically, GA biosynthesis genes strongly influence runner formation. Transcription factors such as LAM, SOC1, and HAN have recently been identified as key regulators. However, the genetic control of runner formation in strawberries, especially for cultivated octoploid strawberry cultivars, is not yet fully elucidated. This review synthesizes current knowledge on the environmental and genetic regulation of strawberry runner induction, providing a theoretical foundation for artificial control of runner formation.